Evaluation of Risk Factors Causing Diagnostic Delay in Non-steroidal Anti-inflammatory Drug-exacerbated Respiratory Disease - Melek Cihanbeylerden; Hazal Kayıkçı; Çise Tüccar; Ebru Damadoğlu; Gül Karakaya; Ali Fuat Kalyoncu (Thoracic Research and Practice)
OBJECTIVE: Non-steroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (N-ERD) can be difficult to diagnose due to the heterogeneity of phenotypes and a lack of validated in vitro tests. This study aimed to provide a better understanding of the course of N-ERD disease, analyze whether there was a delay in clinical diagnosis, and explore the factors that might cause diagnostic delay. MATERIAL AND METHODS: This observational, cross-sectional, study included patients aged over 18. The time taken by clinicians to diagnose N-ERD was recorded as the clinician diagnosis time, while the time taken by patients to complete the N-ERD triad was recorded as the actual diagnosis time. A difference of six months or longer between actual diagnosis and clinician diagnosis times was accepted as diagnostic delay. Statistical analyses were performed to ascertain the parameters that could cause this delay. RESULTS: The study included a total of 107 patients diagnosed with N-ERD. The patients had been diagnosed with chronic rhinosinusitis with nasal polyps, asthma, and NSAID hypersensitivity for an average duration of 14.9±9.6, 14.3±9.9, and 11.7±9.3 years, respectively. Thirty-nine (36.4%) of the patients had a delayed diagnosis. The mean delay in the diagnosis of N-ERD was 7.4±6.6 (2.0-12.0) years. Delayed diagnosis showed a correlation with thyroid dysfunction (P = 0.021), while it did not have a significant relationship with the remaining factors. CONCLUSION: The results of this study have indicated delays in diagnosing N-ERD patients and emphasized the need for adequately recognizing the disease to initiate timely, appropriate treatment.